DisOrientations : German-Turkish Cultural Contact in Translation, 1811-1946. - Dickinson, Kristin (Penn State University Press, 2021)
"Explores the German-Turkish literary-cultural relationship from 1811 to 1946, focusing on literary translation as a complex mode of cultural, political, and linguistic orientation"-- Provided by publisher.
Description based upon print version of record.
Keywords: German literature -- Translations into Turkish -- History and criticism.; Turkish literature -- 20th century -- Translations into German -- History and criticism.; Turkish literature -- 19th century -- Translations into German -- History and criticism.; Germany -- Relations -- Turkey.; Turkey -- Relations -- Germany.; Littérature allemande -- Traductions turques -- Histoire et critique.; Littérature turque -- 20e siècle -- Traductions anglaises -- Histoire et critique.; Littérature turque -- 19e siècle -- Traductions allemandes -- Histoire et critique.; Allemagne -- Relations -- Asie mineure; Asie Mineure -- Relations -- Allemagne.; LITERARY CRITICISM / Comparative Literature.; International relations; Turkey; Germany; 1800-1999; Criticism, interpretation, etc.